Optimizing Students' Writing by Using Chat GPT - Alrina Raras Tacazely; Muhammad Aulia Taufiqi Aulia (Foreign Language Instruction Probe, 2024)
ChatGPT has become increasingly popular in recent times due to its utilization of AI technology, surpassing Google in terms of effectiveness. It is also widely used by students as a valuable learning tool. When learning English, ChatGPT can aid in translating passages and evaluating students' writing. This study aimed to assess the impact of ChatGPT on students' writing skills. The results demonstrated that students were able to identify their writing mistakes through the use of ChatGPT. Not only did ChatGPT provide corrections, but it also offered comments on their writing, facilitating easy revision. Furthermore, students exhibited improved writing when compared to using Google Translate. While Google Translate merely translates the text, ChatGPT provides suggestions for enhancing the writing, resulting in more cohesive compositions. However, students argued that Google Translate was more convenient because it allowed for automatic translation by simply taking a picture of their writing. In contrast, ChatGPT requires manual typing of the text. It is worth noting that although Google Translate offers convenience, ChatGPT provides valuable guidance for better writing. In conclusion, ChatGPT can serve as an alternative for teaching writing. Teachers can encourage students to utilize ChatGPT to evaluate their writing, ensuring that they do not overly rely on it and make progress in learning English. By striking a balance between independent writing skills and the assistance of ChatGPT, students can enhance their overall language proficiency.